Molecular characterization of aedes albopictus (diptera:culicidae) from hot spot dengue-infested areas / Siti Nazrina Camalxaman, Prof Madya Rodziah Ismail and Dr. Nazri Che Dom - Camalxaman, Siti Nazrina; Ismail, Rodziah; Che Dom, Nazri (Research Management Institute (RMI), 2013)
Laboratory work and thesis writing has been completed within one and a half years. The aim of this study is to characterize the genetic diversity and evolutionary relationship of Ae. albopictus collected from dengue cluster areas based on the CO1 gene as a genetic marker. Local sequences will be amplified and compared, results obtained will help determine the genetic diversity, geographic origin and future expansion of Ae. albopictus. The distribution and infection frequencies of Wolbachia in local Ae. albopictus is currently unknown also forms the basis of this study. Broadly, findings from this study are expected to provide a new perspective aimed to improve current vector control and surveillance program. One of the approaches that could mitigate the spread and threat of dengue would be by improving the current understanding of the vector biology and enhancing vector control strategies. This in turn necessitates the need to characterize the vector itself, and the determination of the prevalence of Wolbachia in these vectors for biological control based approaches (Bonizzoni, Gasperi, Chen, & James, 2013). Wolbachia is an endosymbiotic alpha-proteobacteria that infects more than 70% of insect species worldwide including a variety of arthropods (Miller, 2013). The potential of Wolbachia to manipulate various functional systems of its hosts affects several aspects of host biology, physiology, immunity, ecology and evolution as well as reproductive properties including feminization, parthenogenesis, male killing and most commonly, cytoplasmic incompatibility (CI) (Werren, 1997). This intracellular bacteria functions as reproductive parasites and has been proposed for the future development of a symbiont-based control approach to tackle Ae. albopictus population (Bourtzis et al., 2014). In tandem, data regarding the natural infection frequency of Wolbachia in Ae. albopictus and the effectiveness of its transmission rates are essential to evaluate its use as a candidate vehicle to modify vector populations (Mains, Brelsfoard, Crain, Huang, & Dobson, 2013). Morphological characterization using DNA barcoding methods that utilize cytochrome oxidase subunit I (CO1) gene has been widely used in the past to attain information regarding mosquito taxonomy (Besansky, Severson, & Ferdig, 2003; Meier & Zhang, 2008). In addition, it has also been used for diagnostic purposes of specific target species. Most research to date focuses on spatial distribution and abundance of Aedes vectors, but scarce information exists regarding the phylogenetic and evolutionary relationship among the vectors at specific localities in Malaysia. Recently, a temporal model using climate variables was developed to forecast dengue cases in Subang Jaya (Dom, Ahmad, Latif, & Ismail, 2013). This model proved to be useful in predicting dengue cases and reinforces previous studies using different modalities and risk assessment methods (Dom, Ahmad, Latif, Ismail, & Pradhan, 2012a; Dom, Latif, Ahmad, Ismail, & Pradhan, 2012b). Such hotspots described by Dom et al. (2013) could now serve as a platform to determine the prevalence and distribution of both the DENV and the vector of choice.